Stability-Indicating Method Development and Validation for Simultaneous Estimation of Ombitasvir, Paritaprevir, and Ritonavir in Formulation by Ultra Performance Liquid Chromatography (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Aim of the present research work was to develop a sensitive, precise and robust stability-indicating UPLC method for the simultaneous estimation of ombitasvir, paritaprevir and ritonavir in formulations. The chromatographic separation of mixture of ombitasvir, paritaprevir and ritonavir was attained in isocratic method utilizing a mobile phase of 0.01N Potassium dihydrogen orthophosphate (pH 5.3) and methanol in the proportion of 60:40%v/v utilizing a BEH C18 column which has dimensions of 100 x 3 mm, 1.7m particle size and the flow rate of 0.3 ml/min. The detection system was monitored at 252nm wavelength maximum with 0.2 ml injection volume. The retaining time for ombitasvir, paritaprevir and ritonavir was achieved at 1.765 min, 2.192 min, and 1.326 min respectively. Ombitasvir, paritaprevir and ritonavir and their combined drug formulation were exposed to thermal, acidic, oxidative, photolytic, and alkaline conditions. The present method was validated as per the guidelines given by the ICH for specificity, accuracy, sensitivity, linearity and precision. The developed method was highly sensitive, rapid, precise and accurate than the earlier reported methods. The total run time was decreased to 3.0 min; hence, the technique was more precise and economical. Stability studies directed for the suitability of the technique for degradation studies of ombitasvir, paritaprevir and ritonavir. The projected method can be utilized for routine analysis in quality control department in pharmaceutical trades.